The Influence of Midwife and Family Support on the Utilization of the MCH Book for Pregnant Women at Kalianda Health Center, South Lampung - Ika Fitria Elmeida; Nurlaila Nurlaila; Nurchairina Nurchairina; Eva Berliana (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
r